Surgical Decompression and Postoperative Rehabilitation of Traumatic Thoracolumbar Junctional Spinal Injury; A Demographical Observation in A Tertiary Care Hospital (Bangladesh Journal of Neurosurgery, 2026)
Traumatic spinal cord injury (SCI) is a severely debilitating condition that puts a person into neurological dysfunction and loss of independence, with an increased rate of both mortality and morbidity. Thoracolumbar spine (T11-L2) is one of the most vulnerable locations for injury for its biomechanics. The outcome is more devastating if not treated immediately Materials and Method: This is prospective study where 45 patients were included by selection criteria who were admitted in the Department of Neurosurgery of Chittagong Medical College Hospital (CMCH) with traumatic SCI from T11 to L2 and treated by decompression and stabilization with pedicle screw from July 2023 to January 2024. Results: Overall, the median (interquartile range) age was 28 years, Range (17 to 65 years). There was male preponderance (84.4%) and the male: female ratio is 5.4:1. (28.9%) presented with complete injury. The most commonly reported mode of injury was fall from tree (40%), level of fracture L1 (48.8%) and burst fracture (55.5%) was the commonest type. The median interquartile range (IQR) time interval from injury to admission was 2 days (0.04 to 4.25 days) and from injury to decompression was 9 days (0.03 to 28 days). Conclusions: Management of traumatic thoracolumbar spinal injury is not only a medical issue but a cumulative effort for educational, infrastructural improvement and professional safety law endorsement as well as social and occupational rehabilitation to bring them a quality life.Bang. J Neurosurgery 2024; 14(1): 30-34